Identification and Genomic Characterization of Two Previously Unknown Magnetotactic Nitrospirae - Zhang, Wensi; Wang, Yinzhao; Liu, Li; Pan, Yongxin; Lin, Wei (Frontiers in Microbiology, 2021)
Magnetotactic bacteria (MTB) are a group of microbes that biomineralize intracellular magnetic organelle magnetosomes consisting of membrane-bounded, nanosized magnetite (Fe3O4) and/or greigite (Fe3S4) crystals. MTB affiliated within the Nitrospirae phylum are of great interest because of their formation of up to several hundreds of Fe3O4 magnetosomal crystals and of dozens of sulfur globules in a single cell. Nitrospirae MTB are widespread in aquatic environments and sometimes account for a significant proportion of microbial biomass near the oxic-anoxic transition zone, linking this microbial group to the key steps of global iron and sulfur cycling. Despite their ecological and biogeochemical importance, our understanding of diversity and ecophysiology of magnetotactic Nitrospirae is still very limited because this group of MTB remains unculturable. Here, we identify and characterize two previously unknown MTB populations within the Nitrospirae phylum through a combination of 16S rRNA gene-based and genome-resolved metagenomic analyses. These two MTB populations represent distinct morphotypes (rod-shaped and coccoid, designated as XYR and XYC, respectively) and both form more than one hundred bullet-shaped magnetosomal crystals per cell. High-quality draft genomes of XYR and XYC have been reconstructed, which represent a novel species and a novel genus, respectively, according to their average amino-acid identity values with respect to available genomes. Accordingly, the names Candidatus Magnetobacterium cryptolimnobacter and Candidatus Magnetomicrobium cryptolimnococcus for XYR and XYC, respectively, were proposed. Further comparative genomic analyses of XYR, XYC and previously reported magnetotactic Nitrospirae reveal the general metabolic potential of this MTB group in distinct microenvironments, including CO2 fixation, dissimilatory sulfate reduction, sulfide oxidation, nitrogen fixation or denitrification processes. A remarkably conserved magnetosome gene cluster has been identified across Nitrospirae MTB genomes, indicating its putative important adaptive roles in these bacteria. Taken together, the present study provides novel insights into the phylogenomic diversity and ecophysiology of this intriguing, yet poorly understood MTB group.